2015
DOI: 10.4018/ijbce.2015010104
|View full text |Cite
|
Sign up to set email alerts
|

Finding Impact of Precedence based Critical Attributes in Kidney Dialysis Data Set using Clustering Technique

Abstract: The influencing aspects for kidney dialysis such as creatinine, sodium, urea & potassium levels display a critical part in determining the persistence estimate of the patients as well as the need for undergoing kidney transplantation. Numerous efforts are been through to develop computerized choice making procedure for earlier persistence. This preliminary study finds the impact of significant parameters based on the precedence of parameters suggested by the doctors & using the k-Means algorithm. With … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…The application of appropriate feature selection technique was reported in the details for chronic kidney disease diagnosis [19]. Ravindra et al, have reported the importance of attribute selection for kidney dialysis survival prediction by making use of k-means clustering techniques [20], [21].…”
Section: Related Workmentioning
confidence: 99%
“…The application of appropriate feature selection technique was reported in the details for chronic kidney disease diagnosis [19]. Ravindra et al, have reported the importance of attribute selection for kidney dialysis survival prediction by making use of k-means clustering techniques [20], [21].…”
Section: Related Workmentioning
confidence: 99%